Adobe Creative Suite 5 bible - Padova, Ted.; Murdock, Kelly (Indianapolis, IN : Wiley Pub., 2010)
"The Creative Suite Bible is one of a few books to cover in one volume: Photoshop, Illustrator, InDesign, GoLive, Acrobat Professional 8 and Version Cue. Professional graphic design firms, ad agencies, and publishing houses do not usually work with just one of these programs when creating designs. Rather, they use a collection of illustration, image-editing, and layout programs to build their designs for print or the Web. This book will show readers who have a basic familiarity with Adobe software how to integrate and manage workflow among these applications. Topics covered include: Developing Consistent Color-Managed Workflows, Moving Files Among the Creative Suite Applications, Preparing Files for Print or the Web, Repurposing Documents, Using Creative Suite with Microsoft Office documents, and much more. This book will address issues that arise every day for the working designer or design student"--Resource description page.
pt. 1. Getting started with workflow solutions -- pt. 2. Getting started with design workflows -- pt. 3. Working with objects and images -- pt. 4. Working with type -- pt. 5. Using Creative Suite and Microsoft Office -- pt. 6. Integrating Creative Suite documents -- pt. 7. Preparing documents for deployment -- pt. 8 Deploying documents -- pt. 9. Printing and digital prepress.
Print version record.
English.
John Wiley and Sons
Keywords: Adobe Photoshop -- Handbooks, manuals, etc; Adobe Illustrator (Computer file) -- Handbooks, manuals, etc; Adobe InDesign (Electronic resource) -- Handbooks, manuals, etc; Dreamweaver (Computer file) -- Handbooks, manuals, etc; Adobe Acrobat -- Handbooks, manuals, etc; Flash (Computer file) -- Handbooks, manuals, etc; Fireworks (Computer file) -- Handbooks, manuals, etc; Adobe Photoshop / Handbooks, manuals, etc; Adobe Illustrator (Computer file) / Handbooks, manuals, etc; Adobe InDesign (Electronic resource) / Handbooks, manuals, etc; Dreamweaver (Computer file) / Handbooks, manuals, etc; Adobe Acrobat / Handbooks, manuals, etc; Flash (Computer file) / Handbooks, manuals, etc; Fireworks (Computer file) / Handbooks, manuals, etc; Adobe Acrobat; Adobe Illustrator (Computer file); Adobe InDesign (Electronic resource); Adobe Photoshop; Dreamweaver (Computer file); Fireworks (Computer file); Flash (Computer file); Computer graphics; Web sites -- Design; Computer Graphics; Infographie; Sites Web -- Conception; computer graphics; COMPUTERS -- Computer Graphics; Computer graphics; Web sites -- Design; Computer graphics; Web sites -- Design; Handbooks and manuals